2013 3rd International Conference on Advancements in Nuclear Instrumentation, Measurement Methods and Their Applications (ANIMM 2013
DOI: 10.1109/animma.2013.6727912
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an imaging spectrometer for localization and identification of radioactive sources

Abstract: Spatial localization of radioactive sources is currently a main issue interesting nuclear industry as well as homeland security applications and can be achieved using gamma cameras. For several years, CEA LIST has been designing a new system, called GAMPIX, with improved sensitivity, portability and ease of use. The main remaining limitation of this system is the lack of spectrometric information, preventing the identification of radioactive materials. This article describes the development of an imaging spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There are several different devices available ‘off the shelf’ that demonstrate a higher precision radioactive source localisation. Lemaire et al [ 15 ] demonstrated the radioactive localisation of sources using a gamma camera GAMPIX [ 16 ]. Higher spatial resolution was achieved using MATLAB post-processing with the GAMPIX running in Time over Threshold (ToT) mode.…”
Section: Introductionmentioning
confidence: 99%
“…There are several different devices available ‘off the shelf’ that demonstrate a higher precision radioactive source localisation. Lemaire et al [ 15 ] demonstrated the radioactive localisation of sources using a gamma camera GAMPIX [ 16 ]. Higher spatial resolution was achieved using MATLAB post-processing with the GAMPIX running in Time over Threshold (ToT) mode.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of radioactivity and its localization has become a main issue interesting nuclear industry (nuclear power plants dismantling, radioactive waste management, radiation protection, etc. ), environmental services, public health, homeland security as well as applications in medical imaging diagnosis and treatment [1]. Instruments dedicated to spatial radioactivity localization can be divided into two main categories: imaging detectors and gamma probes.…”
Section: Introductionmentioning
confidence: 99%